Large Lizard Lineup for South Florida [trifold brochure] - Justin Dalaba; Frank Mazzotti (EDIS, 2019)
Non-native reptile species breeding in Florida, tegus, monitors, and iguanas from Africa, South America, Central America, and Mexico, currently outnumber native Florida reptiles. This trifold brochure written by Justin Dalaba and Frank Mazzotti and published by the UF/IFAS Wildlife Ecology and Conservation Department serves as a guide to several commonly confused species. https://edis.ifas.ufl.edu/uw459